Reconceptualizing Fiduciary Guarantee Execution After Indonesia's Constitutional Court Ruling - Tita Jiwanty Fitri; Djumikasih Djumikasih; Herlindah Herlindah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
The Constitutional Court Decisions No. 18/PUU-XVII/2019 and No. 71/PUU-XIX/2021 have reshaped the legal framework of fiduciary guarantee execution in Indonesia by mandating court involvement and debtor consent in cases of default. This study examines the legal reasoning behind these decisions and their implications for the executorial nature of fiduciary certificates. Using a normative legal research method with statutory and conceptual approaches, the research finds that these rulings redefine fiduciary certificates from self-executing instruments to legal documents requiring judicial validation. While this shift enhances procedural justice and debtor protection, it also undermines the efficiency of extrajudicial enforcement, which has been a core feature of fiduciary law. The transformation introduces legal uncertainty for creditors relying on the swift enforcement previously granted by fiduciary titles. The findings suggest the need for a normative reconstruction of the fiduciary execution mechanism to harmonize constitutional values, procedural fairness, and the principle of legal certainty.